Higher! Higher! - Patricelli, Leslie (Somerville, Mass. : Candlewick Press, 2010)
With help from her father and a lot of imagination, a little girl on a swing goes higher than a giraffe, a skyscraper, and even a jet plane.
Cover title.
Boston Globe-Horn Book Honor Winner.
Keywords: Swings -- Juvenile fiction; Imagination -- Juvenile fiction; Swings -- Fiction; Imagination -- Fiction; Board books; Swings -- Fiction; Imagination -- Fiction; Board books